Penerapan Penyusunan Laporan Keuangan Pada Usaha Kecil Menengah Berbasis Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah Pada CV. Primavera - Sarwo Eddy Wibowo, Danil, Elfreda Aplonia Lau (EKONOMIA, 2020)
Preparation of financial statements has an important role, namely for the preparation of planning, control, and decision making. The purpose of this study is to find out and analyze the preparation of balance sheet reports, profit or loss reports and note of financial statements in accordance with the provisions of financial accounting standards for micro, small and medium entities at CV. Primavera.            The research methods used in this study focused on CV. Primavera which focuses on the preparation of financial reports in accordance with the provisions of financial accounting standards for micro, small, and medium entitie (SAK EMKM).            From view the results calculated by Dean J. Champion shows the preparation of balance sheet reports 0% (not suitable), profit or loss reports 50% (unfit), note of financial statements 0% (not suitable).The conclusions of this research, balance sheet reports and note of financial statements not suitable in accordance with the provisions of financial accounting standards for micro, small, and medium entities because CV. Primavera does not prepare balance sheet reports and note of financial statements while preparing profit or loss reports on CV. Primavera not in accordance with the provisions of financial accounting standards for micro, small, and medium entities because CV. Primavera has not calculated the income tax expense and classifies the purchase of material as a burden.